Produksi Bioetanol Dari Pati Sorgum Dengan Variasi Penambahan Tween 80 Dan Waktu Fermentasi - Santoso Nugroho; Elvi Yenie; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Energy consumption is increasing steadily with the population growth and industrial development. Therefore, a substitute should be found. Bioethanol has been pointed out as asolution for variety complex problems related to energy and environmental issues. Sorghum [Sorghum bicolor (L) Moench] is considered to be a viable and renewable feedstock forbioethanol production because it high starch contains. The use of tween 80 as a growth supplement can help alter the substrate structure and make it more accessible to enzim, thuscan improve bioethanol yields. Simultaneous saccharification and fermentation was used to produce bioethanol from sorghum starch using commercial alpha amylase andglucoamylase. The fermentation were done in a 2 L bioreactor in batch mode (T = 20-300C; pH = 4,5). The variabel studied were fermentation time (24, 48, 72 and 96 h) and tween 80(7,5 and 10 ml/l). Bioethanol concentration were analyzed using Gas Ghromatography. The optimum amount of tween 80 to be added was 10 ml/l, which result the highest bioethanolyield 8,74 g/l in 96 h of fermentation.Keywords : bioethanol, tween 80, sorghum starch, simultaneous saccharification and fermentation.